Study of in Vitro Antimicrobial Activity and in Vivo Wound Healing Potentiality of Leaves of Callistemon Viminalis - Avijit Mazumder; Utpal Anand; Saumya Das (Institute of Medico-legal Publications Pvt Ltd, 2022)
Callistemon viminalis, often known as the stream bottlebrush, is a tropical plant in the Myrtaceae familyand is renowned for its ability to grow rapidly in riparian zones. It is exclusively found in New South Wales,Queensland, and Western Australia. The roots of this species are entangled, which helps stabilize the soil, whichreduces the danger of erosion. This plant has antibacterial, antifungal, antioxidant, and other pharmacologicaland insecticidal abilities that are also related to other medicinal properties. This research investigates the benefits,applications, and features of several extracts obtained from components of C. viminalis (branches, flowers, fruits,bark, and leaves). Bioactive compounds were characterized in detail by noting their chemical structures. The useof C. viminalis in folk medicine was fully supported by the results. Collecting and compounding plant materials,including processing, drying, and grinding, and then doing research to screen pharmaceutical effects, are all partof making the cure. Rats had their wound healing ability tested using a method known as in vitro experimentation.This method relies on excision wounds. The capacity of the extracted substance to close wounds when appliedas an ointment was shown to be greater than in the control. The epithelization time in the standard and treatedgroups was significantly shorter than in the basic ointment base treatment group. The group treated with 5% w/wextract ointment had greater traction intensity than the control group (1.96 gm/mm2), with a significant differenceof (1.12) gm/mm2. The tensile strength of the (3.86) gm/mm2 of the 5% w/w treated group. A substantial increasein tensile strength was seen on the tenth day for both the extract level and the normal medicine.